1996
DOI: 10.1038/ng1196-300
|View full text |Cite
|
Sign up to set email alerts
|

Positional cloning of a gene for Hermansky–Pudlak syndrome, a disorder of cytoplasmic organelles

Abstract: Hermansky-Pudlak syndrome (HPS) is an often-fatal autosomal recessive disease in which albinism, bleeding, and lysosomal storage result from defects of diverse cytoplasmic organelles: melanosomes, platelet dense bodies, and lysosomes. HPS is the most common single-gene disorder in Puerto Rico, with an incidence of 1 in 1,800. We have identified the HPS gene by positional cloning, and found homozygous frameshifts in this gene in Puerto Rican, Swiss, Irish and Japanese HPS patients. The HPS polypeptide is a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
350
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(357 citation statements)
references
References 21 publications
3
350
0
1
Order By: Relevance
“…Another 25% of HPS cases on the island occur from a deletion (3,904 base pairs) in HPS3. HPS3 is believed to have developed in the 1880s-1890s in the central mountainous region of Puerto Rico (9,17,19). Consistent with the genetic drift expected over hundreds of years, more recent studies have suggested that carrier frequencies for HPS1 and HPS3 are similar across Puerto Rico (9,20).…”
Section: Genetic and Functional Abnormalitiesmentioning
confidence: 88%
“…Another 25% of HPS cases on the island occur from a deletion (3,904 base pairs) in HPS3. HPS3 is believed to have developed in the 1880s-1890s in the central mountainous region of Puerto Rico (9,17,19). Consistent with the genetic drift expected over hundreds of years, more recent studies have suggested that carrier frequencies for HPS1 and HPS3 are similar across Puerto Rico (9,20).…”
Section: Genetic and Functional Abnormalitiesmentioning
confidence: 88%
“…13 17 ) result from mutations in genes that encode both known vesicle trafficking proteins and novel proteins. In the mouse, seven additional genes 4,5,9,18-21 associated with HPS have been identified.…”
mentioning
confidence: 99%
“…The relatively small genetic interval defined by these studies contained no apparent candidate genes for the disorder, but corresponded to a small enough physical interval to permit a 'positional cloning' approach to identify the HPS gene (32). Once identified, the HPS gene was found to span 30.5 kb of DNA and consist of 20 exons, the first two of which are entirely noncoding (33).…”
Section: The Hps Gene and Mutationsmentioning
confidence: 99%
“…No HPS mRNA is detectable from this mutant allele (39), indicating that HPS mRNA is subject to the so-called 'nonsense-mediated decay' of aberrantly-translated mRNAs. Most Puerto Rican HPS patients are homozygous for the codon 491-496 duplication (32,35,39), although HPS has not been reported elsewhere in the Caribbean, suggesting that this HPS gene mutant allele probably arose on or was introduced to the island of Puerto Rico early during its history and became frequent by chance and occult inbreeding; there is no evidence for any selective Pigment Cell Res. 13,2000 As shown in Table 1, mutations in a number of the other mouse HPS-like loci have also been found.…”
Section: The Hps Gene and Mutationsmentioning
confidence: 99%
See 1 more Smart Citation